Analisis Kesulitan Belajar Siswa Kelas III Sekolah Dasar dalam Kemampuan Berhitung melalui Metode Observasi - Fitria, Dewi; Wulandari, Yunita; Hidayat, Rahmad (Lembaga Yasin AlSys, 2023)
The problem that is often faced by every student is the massive learning difficulties faced by children, especially at elementary school. So research is needed to study this matter. So this research aims to examine students’ learning difficulties in learning mathematical calculations. To achieve this goal, this research uses a qualitative method with a case study type of research which aims to understand a particular case in depth. Difficulty learning to calculate mathematics experienced by students if left untreated will have a negative impact on students both in daily life, education, and also on future career paths. The results obtained from the research students, namely class III students, include difficulty in counting, difficulty pronouncing sequential numbers, ability to differentiate number, and ability to understand the concept of counting.